THE EFFECTIVENESS OF FLIPPING CLASSROOM MODEL ON EFL SECONDARY SCHOOL SPEAKING SKILLS - Yahya Ashour Alkhoudary; Jehad Ashour AlKhoudary (University of Kuningan, 2019)
This study examines the impact of flipped learning on ESL students' speaking skills. Basically, secondary school students lack out-of-class instruction to review and study teaching materials independently since there is no opportunity to practice speaking skills outside the class. Therefore, the availability of the technological device in everyone's hand may help to enhance speaking if they are monitored regularly. The qualitative and quantitative approach is employed. The participants consisting of (40) Omani secondary school students, were divided into two groups (20) in the Experimental Group (E. G) and (20) in the Controlled Group (C.G). Pre-and post-tests were managed to both groups before using flipped classroom (FC) as a scaffolding of teaching speaking to non-native learners. Besides, a questionnaire was administered to. The results revealed that E.G excelled in the C.G. Also, it showed a positive attitude towards flipping as a learning strategy.